Public opinion and criminal justice - Wood, Jane L.; Gannon, Theresa A. (Willan, 2009)
Public opinion is vital to the functioning of the criminal justice system but it is not at all clear how best to establish what this is, and what views people have on different aspects of criminal justice and the criminal justice system. Politicians and the media often assume that the public wants harsher, tougher and longer sentences, and policies may be shaped accordingly. Detailed research and more specific polling often tells a different story. This book is concerned to shed further light on the nature of public views on criminal justice, paying particular attention to public opinion towar